(untitled) (Global Journal of Science Frontier Research, 2023)
The Jurassic lithostratigraphy of the Mixtec Region is relatively well known however the system on which is based includes formational descriptions somewhat deficient e g vagueness characterization by fossil content insufficient cartographic discrimination In order to contribute to correct such deficiency we undertook a detailed study of the R o um Area vicinity of Tlaxiaco where the Middle Jurassic units that make up the Tecocoyunca Group display their attributes thus allowing to supplement the formational descriptions It was found that locally the Tecocoyunca Group includes in the lower part the associated Formations Zorrillo Taberna Early to Late Bajocian consisting of 287m of carbonaceous siltstone mudstone and subarkosic very fine-grained sandstone and siltstone this composite unit bears pelecypods and continental plants as well as two carbon zones it is interpreted that they were part of a delta complex These associated formations conformably underlie the Sim n Formation Middle-Late Bathonian it consists of 270m of subarkoses and siltstone set in thin to thick strata it is interpreted as a transitional deposit This unit concordantly underlies the Otatera Formation Late Bathonian consisting of 170m of pelecypod coquina with intercalations of spathite limestone strata it is regarded as shallow neritic deposit with a subordinate beach component This unit concordantly underlies the Yucu uti Formation Middle Callovian constituted by 118m of fine-grained sandstone coquina and biomicrite that bear pelecypods it is interpreted as transitional to shallow neritic deposit This unit unconformably overlain the Oxfordian Limestone with Cidaris which is no part of this Group The Tecocoyunca Group includes a paleofauna and paleoflora constituted by Middle Jurassic mollusks and plants common throughout the Mixtec Region Finally it is thought that the detailed descriptions of the formations making up the Tecocoyunca Group are in fact an advance in the redefinition of the Mixtec Region s Middle Jurassic units